Can geopolymer mixture be a solution for utilizing waste glass and basic oxygen furnace slag as aggregates? - Manap Islambek; Galymzhankyzy Anel; Omarova Zhaniya; Ualiyev Dulat; Temirbekov Doszhan; Shon Chang-Seon; Zhang Dichuan; Kim Jong Ryeol (E3S Web of Conferences)
This research studies the influence of aggregate proportions, namely Waste Glass Sand (WGS) and Basic Oxygen Furnace Slag (BOFS), on the expansion and compressive strength characteristics of both geopolymer and Ordinary Portland Cement (OPC) mixtures. The research includes an experimental program in which geopolymer mixtures were prepared with different combinations of WGS and BOFS contents (0/100, 25/75, 50/50, 75/25, 100/0, respectively) alongside reference OPC samples containing only WGS or BOFS. The samples prepared for testing expansion behavior were cured under 2 conditions: water submersion and 1M NaOH solution submersion, both maintained at 80°C. Regardless of different combinations of SWS and BOFS, the 28-day compressive strength results for all geopolymer mixtures exceeded the value of 40 MPa. The geopolymer samples experienced different expansion patterns depending on factors such as aggregate content and curing conditions. Specifically, a mixture with 25% WGS and 75% BOFS showed rapid expansion in water, while others maintained expansion within acceptable limits (0.1% threshold value). This was analyzed via literature review, highlighting the role of the alkali-silica reaction. At the same time, the OPC mortar mixture demonstrated significant expansion values, particularly in the NaOH solution, which is connected to the interaction between cement hydration products and NaOH. Based on compressive strength and expansion results, the geopolymer mixture having the 50/50 combination of WGS and BOFS seems to be the optimum mixture in compressive strength and expansion behavior.